(untitled) (Revista Brasileira Multidisciplinar, 2024)
The use and abuse of drugs puts the individual’s health at risk, thus leaving them exposed and vulnerable to the psychoactive effects of these substances. Throughout history, drug use has been a very old fact where the number of users is increasing more and more. Psychoactive substances are drugs that act on the central nervous system (CNS), which are capable of modifying the biochemical mechanisms of the brain. Cocaine is obtained by extracting the leaves of the vegetable Erytroxylum coca and is classified as a tropic alkaloid. It is known that the cocaine trafficked on the streets is not completely pure. Various easily obtainable and low-cost substances are added in order to increase their final volume and therefore maximize the profitability of the illegal trade. The objective of this work was to identify the main adulterants and verify the chemical profile of the samples seized by the Civil Police-PB. Therefore, a qualitative and descriptive analysis of the analytical results already existing at the Scientific Police Institute - PB was carried out. 165 samples were analyzed, of which more than 60% were positive for cocaine and about 30% contained only an adulterant. It was observed that most samples were adulterated and the main adulterants were caffeine, creatine, phenacetin, sodium bicarbonate and sucrose. In addition, there was a change in the chemical profile of the samples during the years 2018–2021. With the results obtained, it was possible to contribute to a deeper knowledge of the chemical profile of the samples seized in Paraíba.